2018
DOI: 10.1007/s00068-018-0966-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of chest tube malposition in trauma resuscitation: single-center experience

Abstract: Patients with malposition of emergency chest tubes according to CT were not associated with worse outcomes compared to patients with correctly positioned tubes. Early emergency chest CT in the initial evaluation of severely injured patients allows precise detection of possible malposition of chest tubes that may require immediate intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Regarding patients who received chest tube replacement after CT due to functionality issues or malposition, these patients presented with poorer P/F ratios and higher TTS scores than patients receiving chest tube placement after CT only or before CT only, whereas the 30-day mortality rates were comparable. This is in line with a previous study from our center, in which major trauma patients with malposition of chest tubes on initial CT did not show worse outcomes compared to patients with correctly positioned tubes [33].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding patients who received chest tube replacement after CT due to functionality issues or malposition, these patients presented with poorer P/F ratios and higher TTS scores than patients receiving chest tube placement after CT only or before CT only, whereas the 30-day mortality rates were comparable. This is in line with a previous study from our center, in which major trauma patients with malposition of chest tubes on initial CT did not show worse outcomes compared to patients with correctly positioned tubes [33].…”
Section: Discussionsupporting
confidence: 92%
“…Manuel F et al documented chest tube malposition in 42% of patients who had emergency admission after trauma and needed chest tubes. In his study Manuel found that chest tubes were in the pleural space in 58% of the cases; while malposition were intrafissural positions in (27%), intraparenchymal positions in (11%) and extra pleural positions in (4%) [ 21 , 22 ]. In his study Kun-Eng Lim et al documented 28 chest tube malposition among the 76 chest tubes that were placed in 54 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In his study Kun-Eng Lim et al documented 28 chest tube malposition among the 76 chest tubes that were placed in 54 patients. Among the 28 malposition, 23 tubes were in the intrathoracic location (20 intraparenchymal; 3 intrafissural) and 5 tubes were in the extra thoracic location (4 in mediastinum; 1 in chest wall) [ 22 , 23 ]. Tube clotting, especially in smaller tubes, is a common cause of non-functioning drainage [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malposition occurs in approximately 30% of the cases during chest tube insertion. The intrafissural position is the most frequent tube location, followed by the intraparenchymal and extrapleural positions (3,4). As mentioned earlier, tension pneumothorax or massive hemothorax was suspected as no breathing sounds were heard on both sides; therefore, bilateral tube thoracostomy was performed.…”
Section: Discussionmentioning
confidence: 96%